Critical Care of Eclampsia with Partial HELLP Syndrome in Resource-Limited Setting: A Case Report - Rizqhan, Muhammad; Wiedjaja, Aryasena Andhika (MEDICINUS, 2025)
Background: Eclampsia is a hypertensive disorder of pregnancy characterized by life-threatening seizures and often requires intensive care among obstetric patients. HELLP (hemolysis, elevated liver enzymes, low platelets) syndrome is a complication of hypertensive disorders in pregnancy, marked by hemolysis, elevated liver enzymes, and thrombocytopenia. Developing countries have high maternal mortality rates due to inadequate antenatal maternal care services.Case Report: Mrs. D, 25 years old, married, a housewife, was referred to the emergency unit of Encik Mariyam Regional Hospital, Lingga, with seizures and decreased consciousness for the past 3 hours prior to admission. The patient wasdiagnosed with eclampsia complicated by partial HELLP syndrome and was scheduled for an emergency cesarean section (SC) by the obstetrician. General anesthesia was administered, and the patient received care in the intensive care unit (ICU) for 5 days under resource-limited conditions.Conclusions: Maternal mortality due to eclampsia and HELLP syndrome accounts for a significant proportion, especially in developing countries. Early diagnosis and prompt treatment by the ICU team can prevent complications and reduce morbidity and mortality. Emerging complications require early multidisciplinary intervention and treatment, including ventilator support, intensive monitoring, and the use of vasoactive medications, all of which can mitigate the progression of organ dysfunction and improve prognosis.